Evaluation of disease activity in rheumatic patients by leucocyte adhesiveness/aggregation. Issue 6 (June 1988) - Berliner, S; Fried, M; Caspi, D; Weinberger, A; Yaron, M; Pinkhas, J; Aronson, M
Abstract : Previous work has shown that leucocyte adhesiveness/aggregation (LAA), as measured by the leukergy test, correlates well with disease severity in rheumatic patients. As LAA is probably a manifestation of the acute phase reaction various components of the acute phase reaction were measured in order to identify the best marker of disease activity. In addition to LAA, the following variables were measured in 79 patients with various rheumatic diseases and in 10 controls: white blood cell and platelet counts, erythrocyte sedimentation rate, haptoglobin, fibrinogen, C reactive protein, albumin, globulin, caeruloplasmin, alpha 1, alpha 2, beta, and gamma globulin, and haemoglobin concentrations. Patients were graded according to the state of their disease as mild, moderate, or severe. The extent of leucocyte adhesiveness/aggregation in peripheral blood proved to be the best laboratory variable for the grading of disease activity. Correct grading was obtained in 63% of the patients by means of the LAA, compared with 48% with C reactive protein, 41% with caeruloplasmin, 40% with haptoglobin, and 32% with haemoglobin. It is suggested that LAA of the peripheral blood during inflammation may be used as a reliable marker of disease severity.